She Bloomed in the Dark: Shadow Feminism and Queer Failure in Paula Gunn Allen’s The Woman Who Owned the Shadows - Kongerslev, Marianne (American Studies in Scandinavia, 2022)
This article analyzes Paula Gunn Allen’s 1983 novel The Woman Who Owned the Shadows deploying Jack Halberstam’s notion of queer failure, a subversive phenomenon that involves embracing negative affects, refusing success narratives, and negating selfhood. Refusing stereotypical feminine positionality in a masculinist universe in favor of a shadowy, female-centered spirit community, the main character, Ephanie, rejects disciplinary gender norms and fails to perform a cis-hetero feminine identity. Recasting Allen’s conception of the medicine-dyke as a Halberstamian shadow feminist, the article analyzes how the novel employs queer failure as a critique of settler colonial oppression and violence, from the main character as failed ciswoman to the novel’s narrative as a failure of form and convention. Through a fragmented narrative style that never truly resolves, the novel lacks stability and familiar structure, challenging the telos of stabile identity formation and the logic of success. Like its main character, the novel is subversive, a queer unstory that fails to adhere to literary conventions, emphasizing unbeing, undoing, and murky kinds of feminist resistance.